Design of Experiments for the Establishment of the Dissolution Test Conditions of Rupatadine Fumarate 10 mg tablets - Castillo Henríquez, Luis (2019)
Design of Experiments (DoE) is a statistical model that aims to determine if the factors under study affect the response, and if so, it determines the conditions under which this variable of interest can be optimized. In terms of pharmaceutical technology, independent variables are usually factors of the formulation, while dependent variables are properties of the product or parameters that indicate the performance of the process. Precisely, the dissolution test is a tool of interest for the developers of medicines since it allows them to evaluate the performance of a formulation designed in a solid pharmaceutical form, such as tablets. The present investigation used the design of experiments to establish and optimize the conditions of the dissolution test of a 10 mg Rupatadine fumarate tablets formulation, resulting in the use of HCl 0,1 N (pH 1) dissolution medium and a rotation speed of 100 rpm for the apparatus II USP, which allow the analysis of the product in a reproducible and reliable way.